A Rare Concurrent Presentation of Typhoid Fever with Bacteremia and Pulmonary Tuberculosis - Guo, Shuhua; Liu, Minghsun (Archives of Clinical and Biomedical Research, 2025)
This case report describes an unusual presentation of concurrent typhoid fever and pulmonary tuberculosis (TB) in an 82-year-old female. She was admitted with syncope and dehydration and initially suspected of having pneumonia and a urinary tract infection (UTI). Urine and blood cultures rapidly identified gram-negative rods, while CT imaging showed cavitary lesions in the bilateral upper lobes and left lower lobe. The gram-negative rods were identified as Salmonella enterica subspecies enterica Typhi, and sputum acid-fast bacilli (AFB) PCR and cultures confirmed the presence of Mycobacterium tuberculosis complex. The patient was treated for both typhoid fever and pulmonary tuberculosis. This rare case highlights the clinical challenge of distinguishing whether a single disease process is responsible for multiple symptoms (Occam’s Razor) or if multiple diseases are concurrently affecting the patient (Hickam’s dictum). Here, two distinct infections explained the complex presentation. Although typhoid fever was diagnosed first and could rarely be associated with pulmonary abscesses, cavitary lung lesions are more commonly seen in pulmonary tuberculosis. This case underscores the importance of considering multiple concurrent infections in complex clinical scenarios.